The scarab beetle tribe Pentodontini (Coleoptera: Scarabaeidae: Dynastinae) of Colombia: taxonomy, natural history, and distribution - López-García, Margarita M.; Gasca-Álvarez, Héctor J.; Amat-García, Germán (Zootaxa, 2015)
Pentodontini is the most diverse tribe of Dynastinae (Coleoptera: Scarabaeidae), and most of the genera are restricted to a single biogeographic region. In this work, the taxonomic composition of the Pentodontini in Colombia was determined, and genera and species were diagnosed based on external morphology and male genitalia. Records of 1,580 specimens from 31 departments and 398 localities in Colombia were obtained from 24 species in the genera Bothynus Hope, Denhezia Dechambre, Euetheola Bates, Hylobothynus Ohaus, Oxyligyrus Arrow, Parapucaya Prell, Pucaya Ohaus, and Tomarus Erichson. Oxyligyrus cayennensis Endrödi, Tomarus cicatricosus (Prell), and T. pullus (Prell) are reported for the first time from Colombia. Pucaya punctata Endrödi is reduced to synonymy with Pucaya pulchra Arrow. Possible changes in the classification of Denhezia Dechambre are discussed. Dichotomous keys are provided for Colombian genera and species. Taxonomic descriptions and distribution maps are included for all species.